ANALISIS PUISI UHIBBUKI JIDDAN KARYA NIZAR QABBANI: KAJIAN PSIKOANALISA SIGMUND FREUD - Azizah, Balkis Nur; Saskia, Nur Lailatus; Nashrullah, Nashrullah (Afshaha: Jurnal Bahasa dan Sastra Arab, 2023)
In this era, psychoanalysis is widely used as a research method because it examines aspects of psychological principles that exist in literary works, especially the characters of the main characters. Uhibbuki Jiddan poetry seeks to express a deep sincerity of love to the lover. The purpose of this study is to describe the id, ego, and superego of the character Ana in the poem Uhibbuki Jiddan by Nizar Qobbani with a literary psychology approach. This research is descriptive qualitative research. The data obtained from this study lead to a psychological analysis of the literature contained in the poem Uhibbuki Jiddan. There are three psychological structures of a person contained in the psychology of literature proposed by Sigmund Freud, namely the id, ego, and superego. In the Uhibbuki Jiddan poem, the id attached to the character ‘ana’ appears naturally, the ego exists only to obtain pleasure, satisfaction, or momentary pleasure by prioritizing needs and the superego is shown with the sincerity of love.